PGC-1α or FNDC5 Is Involved in Modulating the Effects of Aβ1−42 Oligomers on Suppressing the Expression of BDNF, a Beneficial Factor for Inhibiting Neuronal Apoptosis, Aβ Deposition and Cognitive Decline of APP/PS1 Tg Mice - Xia, De-Yu; Huang, Xin; Bi, Chong-Feng; Mao, Lin-Ling; Peng, Li-Jun; Qian, Hai-Rong (Frontiers in Aging Neuroscience, 2017)
Alzheimer’s disease (AD) is generally defined as the aberrant production of β-amyloid protein (Aβ) and hyperphosphorylated tau protein, which are deposited in β-amyloid plaques (APs) and neurofibrillary tangles (NFTs), respectively. Decreased levels of brain-derived neurotrophic factor (BDNF) have been detected in patients with AD compared to control subjects. However, the underlying molecular mechanisms driving the downregulation of the BDNF remain unknown. Therefore, we explored the mechanisms underlying the regulation of BDNF in the neurons of APP/PS1 transgenic (Tg) mice, an AD experimental model. Using the APP/PS1 Tg mice, we found that BDNF expression was markedly downregualted at the age of 3- and 9-month-old. After cerebroventricular injection (i.c.v.) of Aβ1-42 oligomers into the mice, BDNF was also found to be decreased, which demonstrated the critical roles of the Aβ1-42 oligomers in regulating the expression of BDNF. In neuronal culture, peroxisome proliferators-activated receptor γ coactivator 1α (PGC-1α) and fibronectin type III domain-containing 5 (FNDC5) were found to be downregulated by treatment with the Aβ1-42 oligomers. In addition, overexpression of either PGC-1α or FNDC5 reversed the suppressive effects of the Aβ1-42 oligomers on the expression of BDNF in neuroblastoma 2a (n2a) cells. More importantly, elevating the levels of PGC-1α, FNDC5 or BDNF in the n2a cells counteracted the effects of the Aβ1-42 oligomers on neuronal apoptosis. Additionally, intranasal administration BDNF in the APP/PS1 Tg mice decreased the Aβ deposition and reduced the cognitive decline of the mice.